Hak Cipta Dan Pendhalang (Studi Tentang Perlindungan Hukum Terhadap Penciptaan Lakon Carangan Di Surakarta) - Pratama, Adityo Putra; , Dr. Kelik Wardiono, SH, M.H; , Inayah, SH, M.H (2014)
Copyright among mastermind with drama, then I have correlated with Act No. 28 of 2014 on Copyright, then I can conclude that the mastermind avoid infringement since the time of the form that has been completed, it is that makes mastermind is not problematic to compose. In the art of puppetry, puppeteer who plays imitation-like grip the book is classified as a puppeteer Wikalpa. The term is the term for the mastermind mastermind who do not have the creation, just like a puppet plays exactly like a book or a play -owned grip another puppeteer, without improvisation at all or do not have the creativity. Relation to the law, the impersonation can be classified as a violation if any work which is imitated tesrsebut known Creator. But the above are included in the category creation composing, other than in accordance with the provisions of article 38 of Law No. 28 of 2014 on Traditional Cultural Expressions which is unknown who explained that everyone is entitled to perform announcement, the validity period of 50 years which is already expired, the mastermind eligible and can transform with new creativity to such work as copyright. So the creation of a manipulator which it is composed are included in the provisions of Article 40 paragraph ( 1 ) letter e , n , and o Law of Copyright.